2021
DOI: 10.3389/fphy.2021.724962
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Spectral Clinical Prototype for Fluorophore Detection

Abstract: Identification of tumour margins during resection of the brain is critical for improving the post-operative outcomes. Current methods of tumour identification use 5-ALA, an exogenous precursor, metabolized to fluorescent PpIX in tumour tissue. Although visible under fluorescent microscope, PpIX is easily photo-bleached and tumour tagging is subjective, resulting in tumour under-resection and accelerated recurrence. To address this issue, photo-bleaching resistant and quantitative method is required. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…In this section, a bio-photonics tissue-recognition biopsy device is discussed. A previous version of the work by Lu et al [ 4 ] is presented, and its adaptation into a board with SiPMs is demonstrated.…”
Section: Use Of Care: Tissue Recognition Projectmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, a bio-photonics tissue-recognition biopsy device is discussed. A previous version of the work by Lu et al [ 4 ] is presented, and its adaptation into a board with SiPMs is demonstrated.…”
Section: Use Of Care: Tissue Recognition Projectmentioning
confidence: 99%
“…Aiming to develop a bio-photonics tissue-recognition device for surgical guidance in vivo, Lu et al investigated the introduction of multiple illumination and detection bands [ 4 ]. Specifically, eight illumination sources and eight APDs were used to simultaneously collect DRS and AF spectra to distinguish between healthy and cancerous tissue.…”
Section: Use Of Care: Tissue Recognition Projectmentioning
confidence: 99%
See 3 more Smart Citations